Characterization of HIV-1 molecular transmission network among middle-aged and elderly HIV-1 infected patients in a district of Shanghai, 2018 - 2021 - Yan TANG; Yang LI; Guancong DENG; Panpan CHEN; Xiaofang PAN; Bing ZHAO (Editorial Office of Chinese Journal of Public Health, 2023)
ObjectiveTo characterize dynamic transmission of prevalent subtype strains of human immunodeficiency virus type 1 (HIV-1) through molecular network among HIV/AIDS patients aged 50 years and above in a district of Shanghai. MethodsBlood samples and demographic information were collected from a total of 580 first diagnosed HIV/AIDS patients during 2018 - 2021 in Pudong New Area, Shanghai municipality. After RNA nucleic acid extraction and the amplification of HIV-1 pol gene segment, a phylogenetic tree was constructed with maximum likelihood method and molecular transmission networks were also established with Tamura-Nei 93 pairwise gene distance method for the patients. The characteristics of the molecular transmission networks for the patients of different ages was analyzed. Results HIV-1 strains were successfully sequenced for a total of 518 patients (302 under 50 years and 216 aged ≥ 50 years). At the optimal genetic distance of 1.20%, the overall molecular clustering rate was 49.07% (106/216) for the patients aged ≥ 50 years and significantly higher than 28.48% (86/302) for the patients under 50 (χ2 = 22.903, P < 0.001). For the networks of degree one (or only one sexual partner involved in a network), the proportion of network involvement in the patients aged ≥ 50 years was 23.45% (53/216) ; the proportion was not significantly different between the patients with homosexual transmission (29.21%, 26/89) and those with heterosexual transmission (21.60% , 27/125) (χ2 = 1.617, P = 0.203) but the proportion was significantly higher in the patients with homosexual transmission between spouses or fixed partners (χ2 = 70.166, P < 0.001); similar involvement of the patients aged ≥ 50 years was observed for the networks of degree two and above, with an overall proportion of 23.45% (53/216) and not significantly different proportions of 23.60% (21/89) and 25.60% (32/125) for the patients with homosexual and heterosexual transmission (χ2 = 0.112, P = 0.738). In terms of HIV-1subtype-specific molecular transmission network involvement, the proportion was 63.64% (7/ 11) for subtype C, 33.33% (33/100) for CRF07_BC, 21.43% (3/14) for CRF08_BC, and 14.93% (10/67) for CRF01_AE, with significant difference among the involvement proportions (χ2 = 14.381, P = 0.002). The proportion of the involved patients aged ≥ 50 years and with delayed diagnosis was significantly higher (61.11%, 22/36) for the larger molecular transmission networks of degree four and above (χ2 = 8.176, P = 0.004). The results of univariate logistic regression analysis indicated that the over 50 years old patients having both homosexual and extramarital heterosexual behaviors, with 50 and more sexual partners, and with a sexual partner in the same residential region were at a significantly increased risk of to be involved in a larger molecular transmission network (P < 0.05 for all) . ConclusionFor the HIV-1 molecular transmission networks with the involvement of patients aged 50 years and above, the characteristics of the networks differs by transmission route of the involved patients and the virus subtype; a part of the involved high risk virus carriers could play an important transmission role in large or larger networks.